Protective film growth on tin in perchlorate and citric acid electrolytes - Almeida, CMVB; Giannetti, B. F. (Elsevier B.V., 2001)
Voltammetry has been employed to study the influence of systematic additions of citric acid on the E-I curves of Tin in 0.5 M NaClO4, in order to verify the film growth in the presence of the organic acid and the inhibition of the pitting corrosion of the metal. The minimum concentration of the organic acid needed to change the GI curves is 10(-2) M, in the pH range 1.0-4.0. At pH 3.0 and 4.0, the scan rate dependence on current density, in the potential region of formation and reduction of the film, showed that in a first stage adsorption occurs. In a second stage, the v(1/2) dependence found can he explained by ohmic resistance control. The formation of tin/citric acid complexes, 10(-2) M, is suggested. The pitting inhibition may be due to the formation of a mixed layer of tin in citric acid concentrations higher than 10(-2) oxide and tin citrate complexes on the electrode surface. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: tin; citric acid; voltammetry; fitting corrosion; film growth